Vidangadi Taila Nasya in Management of Vataja Pratishyaya - Heenakausar Ayub Tamboli; Nilakshi Shekhar Pradhan (International Journal of Ayurveda and Pharma Research, 2025)
Vataja Pratishyaya which can be correlated to allergic rhinitis which is a prevalent condition characterized by symptoms such as nasal obstruction, rhinorrhea, sneezing, etc. In Ayurveda, it is classified as a Pranavaha Srotas Vikara (upper respiratory tract diseases), primarily resulting from the vitiation of Vata Dosha, leading to irritation in the nasal passages. This imbalance can be triggered by factors like exposure to allergens, environmental pollutants, and seasonal changes. Acharya Sushruta stated five distinct types of Pratishyaya, among which Vataja Pratishyaya is considered the most prevalent. It is considered a causative factor for various diseases and is given significant importance in Shalakya Tantra. Nasya Karma of Vidangadi Taila through the nostrils, is a treatment chosen for study in Vataja Pratishyaya. The treatment was aimed at pacifying aggravated Vata and Kapha Doshas. This procedure helps in lubricating the nasal mucosa, expelling accumulated Doshas, and restoring balance to the affected Doshas. The present study was planned to evaluate the nature of disease, its course and management with Ayurvedic therapy and to develop evidence-based support for effect of Vidangadi Taila Nasya in Vataja Pratishyaya as mentioned in Gadanigraha.